GAMBARAN TINGKAT KECEMASAN ANGGOTA BINTARA DAN TAMTAMA PRAJURIT TNI-AD YANG MELAKSANAKAN TRADISI SATUAN DI KESATUAN DENKAV 4/SP - Muryani, Ni Made Sri; Muhajirin, Muhajirin (Jurusan Keperawatan Poltekkes Kemenkes Makassar, 2021)
The unit tradition is one of the efforts made by military units to instill pride and a sense of responsibility towards the unit. In the implementation of the unit tradition, there are still problems, namely the presence of new members who experience anxiety when facing the unit tradition. This study aims to determine description of anxiety levels of Bintara and Tamtama Army Soldiers who hold squad tradition in Denkav 4/SP. This study uses descriptive method with quantitative approach using questionnaire measuring instrument and sampling technique used is total sampling with the number of samples as many as 40 respondents. Most tamtama soldiers have a moderate anxiety level with a total of 35%, as well as the majority of petty officers have a moderate anxiety level with a total of 40%. The level of anxiety found in each soldier is classified as moderate so that assistance and guidance from seniors is needed in carrying out the tradition of the unit in order to be more motivated and reduce the impact of anxiety caused